The Role of Women in Contemporary Islamic Education and Da’wah - E Nayab, SYEDA DUR (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2026)
This paper examines the evolving and increasingly prominent role of women in contemporary Islamic education and da’wah, focusing on their expanding participation as educators, leaders, and influential figures within diverse Muslim societies. Historically, women’s involvement in these fields was often limited by prevailing cultural and social norms that restricted their public religious roles. However, recent decades have witnessed significant changes driven by educational reforms, globalization, and the rise of digital technologies, which have opened new avenues for women to engage in learning, teaching, and outreach activities. This study investigates how women navigate the complex balance between religious authority and community expectations, contributing meaningfully to the dissemination of Islamic knowledge and spiritual guidance. This work also takes on the day-to-day struggles of women due to the role society gives them, broader access and the notion of male dominance. The research demonstrates, through case studies from different parts of the world, how women have greatly contributed to new thinking and openness in Islamic teaching and preaching. Having them involved helps religious education to include differences and respond to current issues affecting Muslims across the world. The writer recommends taking steps to strengthen, value and support women to further their work in Islamic scholarship and outreach. Understanding and promoting women’s important contributions within Islamic instruction and da’wah will allow them to adapt, respond well and highlight the variety seen in the present-day Muslim community.